2020
DOI: 10.1111/jppi.12357
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Toward Persons with Intellectual Disability in South America: A Narrative Review

Abstract: People with intellectual disability (ID) form one of the most underserved/stigmatized groups in society. Published data have documented stigma toward this population group in different countries. However, this phenomenon has received scant attention in South American countries. The aim of this work is to conduct a systematic search of published and gray literature in the area of stigma toward persons with ID within the 12 countries of the region to explore expression of stigma toward people with ID in the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Studies have also reported national differences in social acceptance and awareness of ID related to literacy about the condition (Zeilinger et al, 2020). A narrative review presented by a joint UK‐Chile team found that there is a paucity of data available about stigma towards people with ID in South America (Tenorio et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also reported national differences in social acceptance and awareness of ID related to literacy about the condition (Zeilinger et al, 2020). A narrative review presented by a joint UK‐Chile team found that there is a paucity of data available about stigma towards people with ID in South America (Tenorio et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regional epidemiological studies show a higher birth rate of babies with Down Syndrome compared to international rates (2.7/1000 vs. 1.0/1000) (Nazer & Cifuentes, 2011; Potier & Reeves, 2016). Persons with ID form a considerable group in Chile that has, until now, remained largely invisible (Tenorio et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ID is a neurodevelopmental condition characterized by differences in cognitive development and adaptive behavior as determined by standardized assessment procedures [3,4]. While self-advocacy groups have had positive impacts for people with ID [5], they still face barriers to participation due to stigma related to differences in verbal communication and learning difficulties, along with the kinds of support they require [6][7][8]. Adults with ID want to be heard, to participate in their life choices, to be treated as adults and accepted as individuals [2].…”
Section: Introductionmentioning
confidence: 99%
“…Chile has 2.8 million people with disability; 20% of them have intellectual disability (National Disability Service, 2015). People with intellectual disability face high rates of stigma, discrimination and social barriers (Ditchman et al, 2013; Tenorio et al, 2020), hampered by exclusionary legislation, with restricted access to education and health services, low participation, and a weak exercise of their citizen rights (Espejo Yaksic & Lathrop Gómez, 2019; Montero & Lagos, 2011; Rotarou & Sakellariou, 2017). Examples of this exclusion are the high prevalence of forced sterilisation among women with intellectual disabilities (Chacón et al, 2017), legal frameworks allowing for the removal of parental rights based on outdated notions of their incapacity to care for newborn babies, and the rejection of children and adolescents from schools because of neurodevelopmental conditions (Obando & Ochoa, 2020).…”
mentioning
confidence: 99%